2015
DOI: 10.1002/eji.201546043
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β induces the differentiation of human CXCL13‐producing CD4+ T cells

Abstract: In the ectopic lymphoid‐like structures present in chronic inflammatory conditions such as rheumatoid arthritis, a subset of human effector memory CD4+ T cells that lacks features of follicular helper T (Tfh) cells produces CXCL13. Here, we report that TGF‐β induces the differentiation of human CXCL13‐producing CD4+ T cells from naïve CD4+ T cells. The TGF‐β‐induced CXCL13‐producing CD4+ T cells do not express CXCR5, B‐cell lymphoma 6 (BCL6), and other Tfh‐cell markers. Furthermore, expression levels of CD25 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 53 publications
11
81
0
Order By: Relevance
“…A recent study found that TGFβ1 is a key CXCL13-inducing factor in human blood CD4 + T cells, triggering CXCR5 + T cell and B cell migration (28). The work reported here and our other recent experiments (data not shown) found that IL2 deprivation is critical for CXCL13 induction, with TGFβ1 providing a synergistic signal only.…”
Section: Cd3 + Cd4supporting
confidence: 73%
See 1 more Smart Citation
“…A recent study found that TGFβ1 is a key CXCL13-inducing factor in human blood CD4 + T cells, triggering CXCR5 + T cell and B cell migration (28). The work reported here and our other recent experiments (data not shown) found that IL2 deprivation is critical for CXCL13 induction, with TGFβ1 providing a synergistic signal only.…”
Section: Cd3 + Cd4supporting
confidence: 73%
“…+ T cells are well correlated and αIL2 dose dependent (Supplemental Figure 5B). TGFβ1 was recently shown to be critical for inducing CXCL13 expression in naive CD4 + T cells, with IL2 blockade amplifying this TGFβ1 effect (28). In our experiments, TGFβ1 alone plus SEB activation had no effect on CXCL13 expression but, together with IL2 deprivation, elicited a significant increase ( Figure 5B).…”
Section: Icossupporting
confidence: 43%
“…They were characterized by significantly higher expression of GZMA , GZMB , CXCL13 , BATF , HLA genes ( Supplementary Figure 9E ). These cells are likely to represent follicular helper-like CXCL13 producing CD4 cells that are associated with tertiary lymphoid structures (28, 29).…”
Section: Resultsmentioning
confidence: 99%
“…CXCL13 is a lymphoid chemokine that is induced in follicular dendritic cells by TNFa and attracts B and T cells expressing CXCR5 during the development of secondary lymphoid tissue and the formation of germinal centres [112,113]. CXCL13 is also expressed in multiple non-lymphoid organs, including the CNS, where it sustains and is produced by pathogenic CD4 + T cells differentiated in the presence of transforming growth factor b during autoimmune disease [114][115][116], In the CNS, CXCL13 is produced by spinal cord neurons after nerve ligation and by microglial cells and macrophages during inflammation, and can be downregulated by IFN [104]. Expression during viral infection promotes the accumulation of memory B cells and antibody-secreting cells [117][118][119], but has not been associated with more CNS B cells or antibody production during the acute phase of SINV infection.…”
Section: Irf3à/à Mice Develop Fatal Disease After Infection With Wnvmentioning
confidence: 99%